"Autumn Thoughts": Shared Images, Shifting Phrases, and Promiscuous Poetics. (1st January 2021) - West, Stephen H.
Abstract : The famous short sanqu lyric known as "Autumn Thoughts" to the tune "Tianjing sha" has been attributed to Ma Zhiyuan since the late sixteenth century. Despite the skepticism of a long list of important qu scholars from the fourteenth to the twentieth century, this attribution is still repeated in textbooks from grade school to doctoral programs. A careful examination of extant versions from 1309 onward shows some degree of difference, from narrow to wide, dependent on contextual use. Phrases from the lyric may also be found as early as the late twelfth century. By carefully investigating these sources and the way in which the tonal pattern of "Tianjing sha" is expanded, contracted, and exploited in other sources, we can see that the use of the famous phrases making up the poem occurs when context and rhyme come together. This leads one to doubt whether attributable authorship of the lyric is possible, or if it is simply the use of nearly cliché phrases that just happened to combine in exactly the perfect order. This would fit with what we know about the performance tradition and about its tendency for collective and anonymous creation through accretion.